The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1248/bpb.35.273
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Study on Resveratrol

Abstract: Appropriate long-term drinking of red wine is associated with a reduced risk for lifestyle-related diseases such as cardiovascular disease and cancer, making resveratrol, a constituent of grapes and various other plants, an attractive compound to be studied. Historically, resveratrol has been identified as a phytoalexin, antioxidant, cyclooxygenase (COX) inhibitor, peroxisome proliferator-activated receptor (PPAR) activator, endothelial nitric oxide synthase (eNOS) inducer, silent mating type information regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
112
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(118 citation statements)
references
References 96 publications
2
112
0
1
Order By: Relevance
“…Previous studies proved that DNJ-rich MLE has been potentially used to improve lipid profiles in a human study (Doi et al 2000) and to suppress lipid accumulation through activation of the b-oxidation in vivo (Tsuduki et al 2009). In addition, resveratrol has properties to decrease ROS ) and stimulate PPARa involved in fatty acid oxidation (Nakata et al 2012). Moreover, previous studies reported that resveratrol improved insulin resistance by promoting HO-1 protein through mediating Nrf2 level in HepG2 cell (Cheng et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies proved that DNJ-rich MLE has been potentially used to improve lipid profiles in a human study (Doi et al 2000) and to suppress lipid accumulation through activation of the b-oxidation in vivo (Tsuduki et al 2009). In addition, resveratrol has properties to decrease ROS ) and stimulate PPARa involved in fatty acid oxidation (Nakata et al 2012). Moreover, previous studies reported that resveratrol improved insulin resistance by promoting HO-1 protein through mediating Nrf2 level in HepG2 cell (Cheng et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Resveratrol is a parent compound of a family of molecules including glucosides and polymers (Cal et al, 2003), existing in cis and transconfigurations in narrow range of spermatophytes of which vines, peanuts and pines are the prime representatives (Kiselev et al, 2011;Nakata et al, 2012;Neves et al, 2012). Previous studies have reported that resveratrol exerted antitumor activities at various stages of tumor initiation, promotion and progression (Cimino et al, 2012;Stefanska et al, 2012;Whitlock et al, 2012), including in esophageal squamous cell carcinoma (Tang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the in vitro situation, resveratrol activates several anti-aging genes and play anti-oxidative effect to delay cell replicative senescence. 11,13) But in the in vivo study, we administrated resveratrol on 3-month old mice, which is far from aging. Therefore, resveratrol rescued HDF-induced inflammatory response and oxidative stress which will strongly induce renal fibrosis.…”
Section: Hfd and Hg Culture Comparisonmentioning
confidence: 99%
“…7) Activation of SIRT1 protects mice from diet-induced obesity, metabolic disorders and oxidative injury, 8) while SIRT1 inactivation is associated with lipid accumulation, cell injury and diabetic nephropathy. 9,10) Resveratrol (3,5,4′-trihydroxystilbene), a natural plant polyphenol first isolated from the roots of white hellebore, 11) is reported as an activator of SIRT1. 12) Several evidences indicated the therapeutic potential of resveratrol, such as its antioxidant activity, cardioprotective effects and anticancer properties.…”
mentioning
confidence: 99%